Predictors of poor glycaemic control in older patients with type 2 diabetes mellitus - Theng, Cheong Ai; Syed Alwi, Syed Abdul Rahman; Lee, Ping Yein; Chew, Boon How (Universiti Malaysia Sarawak, (UNIMAS), 2015)
We assessed the predictors of poor glycaemic control among older patients with type 2 diabetes mellitus (T2DM) in Malaysia.This cross-sectional study used the data of 21,336patients aged ≥ 60years with T2DM from the Adult Diabetes Control and Management Registry 2008–2009.Predictors of poor glycaemic control were: age groups60–69years (odds ratio [OR] 1.96, 95% confidence interval [CI] 1.66–2.33) and 70–79years (OR 1.43, 95% CI 1.20–1.71); Malay (OR 1.53, 95% CI 1.41–1.66) and Indian (OR 1.32, 95% CI 1.19–1.46) ethnicities; T2DM durations of 5–10years (OR 1.46, 95% CI 1.35–1.58) and > 10years (OR 1.75, 95% CI 1.59–1.91); the use of oral antidiabetic agents only (OR 5.86, 95% CI 3.32–10.34), insulin only (OR 17.93, 95%CI 9.91–32.43), and oral antidiabetic agents and insulin (OR 29.42, 95% CI 16.47–52.53); and elevated blood pressure (OR 1.10, 95% CI 1.01–1.20), low-density lipoprotein cholesterol (OR 1.48, 95% CI 1.38–1.59) and triglycerides (OR 1.61,95% CI 1.51–1.73). Hypertension (OR 0.71, 95% CI 0.64–0.80), hypertension and dyslipidaemia (OR 0.68, 95%CI 0.61–0.75), pre-obesity (OR 0.89, 95% CI 0.82–0.98) and obesity (OR 0.76, 95% CI 0.70–0.84) were less likely to be associated with poor glycaemic control.Young-old and middle-old age groups (i.e.< 80years), Malay and Indian ethnicities, longer T2DM duration, the use of pharmacological agents, and elevated blood pressure and lipid levels were associated with poor glycaemic control. The presence of comorbidities, pre-obesity and obesity were less likely to be associated with poor glycaemic control.